The Development of the Motives for Listening in The First Language by Preschool Children - Nataliia Kharchenko (Психолінгвістика, 2018)
This article presents a psycholinguistic study that aims to elucidate the development of the motives for listening in the first language (L1) by preschool children. The development of the motives for listening by preschool children was studied according to the following criteria: consciousness, stability, and independence. A set of psycholinguistic methodological approaches was used to measure the development of the motives for listening by preschool children. In total, 378 preschool children took part in the present psycholinguistic study. The results of the data analysis revealed several levels that were associated with the development of the motives for listening in the children’s L1. Those levels will be further presented and discussed in the article. To the high level of the motives of listening development were assigned 9,0% of children (n=34), which have the bright motive as a subject of communicative and speaking needs, as the need for sense-forming development. The directness of their listening is directly dependent on the speech motive. They have stable motives, as well as a strong motivation of achievement. To the average level of the motives of listening development were referred 12,3% of children (n=48), in which the communicative and speaking needs, as the needs of the understanding of other people’s opinions are not sufficiently expressed, however, others – non-ideal – objects of need prevail; the speech motive is not at the required stage of development in order to become an objectified need; this is the degree on which the meanings of the speech needs are only begin and the primary acquisition of it is specification as the need for sense-formation. Motives are unstable, non-independent, mostly due to training tasks. This is the state of the initial development of the speech motive. To a level below the average, 52,6% of children (n=198) were identified, which did not reveal the motives of forming meaning, that induced listening; their perception and understanding is polymotivated, it is excited by several motives, predominantly non-verbal ones; the need for communication and speech comprehension are not associated with subsequent speech behavior; the communicative and speaking needs in the sense of the heard remain uncertain and not specified. To a low level of the motive of listening development were assigned 25,5% of children (n=98), in which the auditing needs in meeting communicative requests are realized only in non-verbal kinds of activities.